Is Perth a secure place: a Western Australian field study of Bluetooth security - Ghori, Khwaja Shan-ul-Hasan Dell, Peter (2007)
Bluetooth, a wireless technology for building short-range communication links, poses a number of security risks, including disclosure of confidential data and unauthorised control of functions such as telephony and data services. The use of these devices is increasing, and many Bluetooth devices store sensitive or valuable data. This increases the motivation for intruders to attack devices over Bluetooth connections. This paper reports the extent of the potential for Bluetooth security problems in Perth, Western Australia. It finds that there are many devices potentially vulnerable to attack via Bluetooth, and that it is feasible to easily access a large number of Bluetooth devices for a sufficiently long duration to cause damage. These findings, taken in conjunction with known existing Bluetooth threats and attacks, indicate a very real Bluetooth security risk. The paper concludes with issues to be investigated in future so that corporate IT departments, end users and manufacturers can provide optimum security, thus reducing the potential for successful Bluetooth attacks in the future.